Alcohol consumption and risk of cardiovascular disease, cancer and mortality: a prospective cohort study. - Zhang, Xinyuan.; Liu, Yan.; Li, Shanshan.; Lichtenstein, Alice H.; Chen, Shuohua.; Na, Muzi.; Veldheer, Susan.; Xing, Aijun.; Wang, Yanxiu.; Wu, Shouling.; Gao, Xiang. (Tufts University. Tisch Library., 2021)
Keywords: Alcohol consumption, Cardiovascular disease, Cancer, Mortality, Nutritional epidemiology.; Springer Open.